Professor T. Season 3 [videorecording (DVD)] - Brady, Stephen (Screenwriter); White, Barney; Miller, Ben, 1966-; De la Tour, Frances, 1944- (PBS Distribution, 2024)
The season begins with Professor T in prison after trying to defend DCI Christina Brand. With both of their careers on the line, both have momentous decisions to make. As the Professor struggles in prison, his old colleagues seek out his analysis and insight to help them solve a series of intriguing crimes. But how long can the Professor survive in these conditions?